Pengembangan Model Prediksi Banjir Berdasarkan Akurasi Inflow Dan Outflow Pada Bendungan Bili-Bili: Development of a Flood Prediction Model Based on The Accuracy of Inflow and Outflow at Bili-Bili Dam - Febi, Febi Murdiana; Rachmat Ciptadi; Fajar Arif Nurdin; Husnul Khatimah; Nur Indah Sari (Himpunan Ahli Teknik Hidraulik Indonesia (HATHI), 2024)
The inflow prediction model for Bili-Bili Dam, developed by the Dam Monitoring Center (PMB), has met the validation interpretation criteria, but the data validation values can still be improved. Therefore, this study develops a simulation prediction model using HEC-HMS with the Transform Method Clark to predict the 5-day inflow by inputting predicted rainfall data from BMKG and observed inflow data. To validate the results of the simulation model, data validation analysis is conducted by comparison using the Root Mean Squared Error (RMSE), Relative Error (RE), Nash Sutcliffe Efficiency (NSE), and Correlation Coefficient (R) methods using calibrated and uncalibrated data. The calibration method used in this study is a linear equation with a 7-day data range starting from February 6 to June 23, 2024. The best validation results of the simulated rainfall data from BMKG against the calibrated observed inflow are found in the 1-day ahead prediction period, with an average NSE = 0.761; average R = 0.246; average RE = 7.2%; average RMSE = 26.814, due to the NSE value close to one and the low RMSE and relative error values. Overall, it can be concluded that the comparison of simulated rainfall data from BMKG against observed inflow with a prediction accuracy of 1 day ahead can be used for inflow prediction at Bili-Bili Dam.